Principles and Strategies for Preserving the Cultural Landscape of Qazvin’s Vernacular-Historic Garden Place with a Focus on Built Heritage - Elham Andaroodi; Batoul Sahrakaran (صفه, 2017)
The preservation of cultural landscapes is a multifaceted, interdisciplinary matter, and needs attention to multilayer, interconnected characteristics of landscape. Bearing in mind the listing of many works as national cultural landscapes, a need is felt to adopt an appropriate approach towards their preservation. Taking advantage of reasoning and deductive strategies, the present research tries to investigate domestic and international references and documents including WHC, ICOMOS and NPS, in order to propose principles for preserving cultural landscapes to preserve and comprehensively recreate natural, built and formative human factors influencing long-term historic, sensory-cognitive, cultural, natural, social, vernacular, environmental and economic values, with an interdisciplinary, collaborative nature. Preservation strategies are studied here in the case of Qazvin’s vernacular-historic garden place as a nationally listed work. In order to do so the garden place is introduced as a type of vernacular-historic landscape, with its inflicted damages studied from natural, built, and human angles. The preservation principles emphasise on protecting originality and integrity of the landscape whilst creating new facilities, services and functions, and prioritises vernacular preservation management and gardening in order to reinforce keepers’ connection with the garden place. The present research has extensively explained and located strategies for built heritage such as preservation of original physical elements, empowerment through new functions (such as ecotourism) and new ‘ultra-structures’ (such as gardening service centres), and restoration of damaged parts. The research method for theoretical literature is of descriptive-explanatory type. Analytical methods have been adopted for field studies using means such as studying documents, field surveys and preparing sketches and pictures.